Preoperative Ankle Swelling and the Effect On Postoperative Wound Complications Following Ankle Fracture Surgery - Anthony M. Silva MBBS, MSc, FRACS(Orth), FAOrthA; Helena Franco MD, MMSc, MSurg; Tom P. Walsh BPod MHSc(Pod), PhD; Albert Hohuynh MBBS; Simon Platt MB, ChB, FRCS, FRCS(Tr&Orth) (Foot & Ankle Orthopaedics)
Background Swelling following an ankle fracture is commonly believed to preclude surgical fixation; swelling is thought to be associated with increased wound complications. Delaying surgery until swelling subsides is thought to secure better outcomes, although no guidelines exist to direct surgeons when an appropriate time to intervention is or whether a visual inspection of the swelling is correlated to quantitative measurement. This study aimed to identify whether preoperative ankle swelling influences postoperative wound complications following ankle fracture surgery. Methods This prospective cohort study recruited patients undergoing operative management of closed rotational ankle fractures on a single side (unilateral injury). Individual surgeons determined the time to surgery based on their usual practice. Ankle swelling was measured on a subjective visual scale and then quantitatively using the validated figure-of-8 technique. Follow-up was standardized at 2, 6, and 12 weeks postoperatively. Between-group participant, surgical, and wound characteristics were recorded and analyzed, in addition to the agreement between qualitative and quantitative ankle-swelling measures. Results Eighty participants were recruited. The wound complication rate was 8.75% (n = 7), with only 1 deep infection requiring operative intervention and antibiotic therapy. Wound complication rates were not associated with quantitative ankle swelling ( P  = .76), visual assessment of ankle swelling ( P  = .65), or time to operative intervention ( P  = .27). Increasing age ( P  = .006) and female gender ( P  = .034) were associated with wound complications. Between-group body mass index, experience level of the operating surgeon, and tourniquet time were not statistically significant. Visual assessment of ankle swelling had a poor to moderate correlation to “figure-of-8’ ankle swelling measurements (intraclass correlation = 0.507, 95% CI = 0.325-0.653). Conclusion In this prospective and underpowered study, we did not find that time to surgical intervention or residual swelling at the time of surgery was associated with increased wound complications following fixation of closed unilateral malleolar ankle fractures, including those involving multiple malleoli. Although surgeon discretion was used in determining readiness for surgery, all cases had some delay, which may have influenced results. Visual assessment of swelling showed only moderate correlation with objective measurement, questioning its reliability as a surgical readiness tool. These findings suggest that in carefully selected cases, delaying surgery beyond initial clinical readiness for reasons of residual swelling may not be necessary. Level of Evidence: Level II, prospective cohort study.